Spiraling through the school of life a mental, physical, and spiritual discovery - Ladd, Diane (Hay House, 2006)
The actress, director, writer, and healer offers vignettes from her own life as a guide to others in overcoming obstacles and finding spiritual fulfillment.
Keywords: Ladd, Diane; Actors -- United States -- Biography; Conduct of life; USA; Biografie; Fiktionale Darstellung